Analisis Tingkat Kepuasan Pelanggan dan Loyalitas Pelanggan terhadap Cafe Infinity Coffee - Muhammad Nuruddin Prathama; Muhammad Nur Aidi; Agus Mohamad Soleh (Xplore: Journal of Statistics, 2022)
Cafe and restaurant businesses are some of the most competitive businesses and have a sizeable market in Jakarta. In this case, the restaurant owner must know the wishes and preferences of the buyer. This research was conducted in one of the cafes in Jakarta "Infinity coffee", this study was conducted to identify consumer characteristics, customer satisfaction, and consumer loyalty. Applying customer satisfaction analysis in the Infinity coffee business can increase understanding of what Infinity coffee consumers want and improve the quality of Infinity coffee services based on research’s results. The analytical methods used in this study are descriptive analysis, Important Performance Analysis (IPA), and the Consumer Satisfaction Index (CSI) as well as correspondence analysis. The results of this study indicate that the entire Infinity coffee service satisfaction index for all aspects is above 80%, which means that the value is included in the satisfied category. However, the IPA scatter diagram shows that there are attributes with a high level of importance that need to be improved in terms of service quality. One of the most important attributes that become a priority for improvement is the attribute of completeness of supporting facilities and adequate cutlery. The Method that used was proven to be successful in examine level of consumer satisfaction also to know more about the characteristic of the consumer.